1981
DOI: 10.1007/bf03339420
|View full text |Cite
|
Sign up to set email alerts
|

The Heat Treatment of Vanadium-Modified Alloy Steels

Abstract: SUMMARY INTRODUCTIONAt a recent symposium, Robinson l summarized the development of and the challenges faced by alloy steels in the automotive industry. Through the years since Henry Ford revolutionized car manufacture, constant changes in alloy steel compositions, to meet the demands of the times, were prevalent. At present, it appears that the technology of heat-treated alloy steels has reached its maturity, with work concentrated on both accurately predicting hardenability from chemical composition and bala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…For the annealing condition of 800 o C 0 s, velocity of grain boundary is estimated using first order approximation [63] as explained below. Apart from Mn solute drag effect on recrystallization, there could be other direct (for example, Mn-C dipole formation [77]) or indirect factors (for example, precipitation [66,[78][79][80][81][82][83] or texture [84]) of Mn solute atoms on recovery/recrystallization mechanism. Ushioda et al [77] have studied the role of Mn in delaying the recovery during annealing, where dissolved C from cementite combines with Mn to form Mn-C complex.…”
Section: Competition Between Recrystallization and Precipitation In Base And Ti+ Gradesmentioning
confidence: 99%
See 1 more Smart Citation
“…For the annealing condition of 800 o C 0 s, velocity of grain boundary is estimated using first order approximation [63] as explained below. Apart from Mn solute drag effect on recrystallization, there could be other direct (for example, Mn-C dipole formation [77]) or indirect factors (for example, precipitation [66,[78][79][80][81][82][83] or texture [84]) of Mn solute atoms on recovery/recrystallization mechanism. Ushioda et al [77] have studied the role of Mn in delaying the recovery during annealing, where dissolved C from cementite combines with Mn to form Mn-C complex.…”
Section: Competition Between Recrystallization and Precipitation In Base And Ti+ Gradesmentioning
confidence: 99%
“…It is proposed that higher amount of Mn solutes increases the solubility of TiC precipitate in austenite phase [82,83] and delays precipitation kinetics. The effect of Mn solute content on precipitation kinetics in the austenite phase is well known [66,[78][79][80][81][82][83], however there are not any conclusive data published on the Mn solute content effect on the precipitate solubility in the ferrite phase. The equilibrium precipitate volume fraction is plotted for the three grades for equilibrium state as shown in Fig.…”
Section: Competition Between Recrystallization and Precipitation In Base And Ti+ Gradesmentioning
confidence: 99%
“…Previous studies reported contrasting results regarding the effect of vanadium on steel hardenability. Grossman, Lamont and Mangonon [6][7][8][9][10] found that vanadium can effectively improve the hardenability of steels; their results showed that the hardenability multiplying factors of steels containing 0.1% vanadium can reach 1.2-1. 6.…”
Section: Introductionmentioning
confidence: 96%